2013
DOI: 10.1016/j.jpainsymman.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Training Intervention for Health Care Staff in the Provision of Existential Support to Patients With Cancer: A Randomized, Controlled Study

Abstract: Context: When a patient receives a cancer diagnosis, existential issues become more compelling.Throughout the illness trajectory, cancer patients could be cared for on oncology wards, by home care teams or in hospices. Nurses working with these patients are sometimes aware of the patients' existential needs but do not feel confident when discussing these issues.Objectives: To determine the effects of a training intervention, where the focus is on existential issues and nurses' perceived confidence in communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 24 publications
4
58
0
4
Order By: Relevance
“…Another study [38] used theoretical training in existential issues combined with group reflection to achieve greater understanding and communicative confidence when caring for patients dying of cancer. That study showed a significant increase in the training group, even after 6 months, compared to the non-training group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [38] used theoretical training in existential issues combined with group reflection to achieve greater understanding and communicative confidence when caring for patients dying of cancer. That study showed a significant increase in the training group, even after 6 months, compared to the non-training group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to face DHD without fear, and reduce avoiding talking about DHD, personal development and confidence are very important for SPC‐HPs . Training including (self‐)reflection is seen as effective to raise confidence in communicating about existential concerns like DHD . Courses may adapt recommendations for counseling psychologists and include basics in suicide risk assessment as well as practical modules .…”
Section: Discussionmentioning
confidence: 99%
“…It emphasizes people’s freedom in making life choices and helps them work toward their values and derive meaning for personal growth (Tan & Wong, 2012). Empirical evidence has shown promise with this approach (Henoch, Danielson, Strang, Browall, & Melin-Johansson, 2013). With evidence from this study, it would be helpful to examine the efficacy and effectiveness of integrating this humanistic-existential framework with more standard cognitive-behavioral interventions in a population of African Americans impacted by multiple forms of trauma.…”
Section: Discussionmentioning
confidence: 99%